Preserving white hegemony: Skilled migration, 'Asians' and middle-class assimilation - Stratton, Jon (Borderlands, 2009)
This article argues that the emphasis on asylum seekers is a distraction in the context of the overall considerations of Australia’s migration policy. The article discusses the development of the 457 visa and the role of international students in developing Australia’s skilled migration program and goes on to consider the relationship between the policy of multiculturalism and the practice of assimilation for non-white migrants entering Australia’s middle class. To this end, the article introduces the ideas of ‘model minority’ and ‘honorary whiteness’ into discussions of the Australian situation.